Conceptual, methodological and ethical issues in children's research in Portugal - Fernandes, Natália (2011)
Methodological issues in research with children have sparked a growing interest by the Sociology of Childhood since the last decades. In Portugal, this interest is more recent, but it has had a significant increase. Considering several researches, namely master thesis, supervised by the authors on the framework of Sociology of Childhood, this proposal intends to characterize some methodological complexities in research with children in Portugal, when we consider their voice and agency in the knowledge producing about them. The goal of this paper is to contribute to the methodological discussion on research with children through the identification of a set of challenges related to: (i) the diversity of methodologies uses in children’s research, (ii) ethical concerns and (iii) the role of the researcher.